Synthesis of substituted anilines via a gold-catalyzed three-component reaction. Issue 4 (6th November 2020) - Ueda, Hirofumi; Yamamoto, Ryota; Yamaguchi, Minami; Tokuyama, Hidetoshi
Abstract : A three-component reaction for the synthesis of substituted anilines by a gold(i )-catalyzed domino reaction was developed. Abstract : A three-component reaction for the synthesis of substituted anilines by a gold(i )-catalyzed domino reaction was developed. Cationic gold catalysts selectively and sequentially activated two different alkynes, which were involved in pyrrole synthesis and subsequent Diels–Alder reaction. The sequential formal (3 + 2) annulation/Diels–Alder reaction of three components provided a variety of substituted anilines in a modular fashion. Moreover, utility of the aniline products was demonstrated by derivatization to substituted benzoxazines, which are pharmaceutically important heterocycles.